EFEKTIVITAS THE TECHNIQUE OF PRACTICABLE POSES DALAM PERUBAHAN PERILAKU KORBAN PENYALAHGUNAAN NAPZA DI INSTITUSI PENERIMA WAJIB LAPOR NAZAR MEDAN - Wahyuning Dwi Wardani Ndraha; Epi Supiadi; Nurjanah Nurjanah (Peksos: Jurnal Ilmiah Pekerjaan Sosial, 2022)
The technique of practicable poses is the result of engineering behavior change technology which is a collaboration of positive reinforcement techniques and behavioral exercises with the aim of reducing the aggressive behavior of immulsive victims of drug abuse who are undergoing a process of social rehabilitation. The purpose of this study is to apply the technique of practicable poses for victims of drug abuse and examine the effectiveness of the engineering technology in reducing aggressive impulsive behavior through psychoeducational sessions, role-playing, peace counseling, relaxation, giving positive reinforcement. Impulsive aggressive behavior is a problem of behavioral deviance in which the individual who experiences it often acts physically and verbally abusive to others, and performs actions quickly without thinking first. The research method used is single subject design (SSD) with a multiple baseline cross subject approach. This study had two subjects with the same problem, namely having aggressive impulsive behavior. The results of applying the technique of practicable poses to two subjects showed a decrease in the intensity of aggressive impulsive behavior. The results of visual observations made by researchers showed that there were continuous changes and a steady decrease in the intensity of aggressive impulsive behavior.